STRATEGI PENGEMBANGAN MUSEUM SUBAK TABANAN SEBAGAI DAYA TARIK WISATA BUDAYA - I Wayan Agus Arif Budi Astina; Ni Wayan Mekarini; Sulistyoadi Jokosaharjo (Universitas Triatma Mulya, 2021)
Museum Subak Tabanan is one regional museum which is held by Dinas Kebudayaan Kabupaten Tabanan since Tabanan has the widest rice field in Bali that cultivate in traditional irrigation system called ‘Subak’. In this Museum, agricultural devices are kept and displayed, but it’s almost forgotten since the pandemi covid 19 known from number of its visitor become low. So here is needed a study to identify the potency as well as strategy to attract more visitor to Museum Subak Tabanan in order this museum can fulfill its function such as keep the artefacts, provide information and educate young generation. Main data is collected by interviewing the management, while supporting data is taken by observation and documentation study is. Data analized by SWOT analysis to find out the strength, weakness, opportunity and threat which later showed four strategies, named strategy SO, ST, WO, WT. The research found out two conclusions: (a) Museum Subak Tabanan has potency to develop such as collection, miniature, film documenter to display in audio visual room, and (b) strategy to be hold to attact more visitors such as create supporting attraction, build MoU with school or other institution, evaluate maintenance and storing system, promotion, and digitalization if possible. It is believed, with its strength and opportunity, it can invite visitor more. The research found out recommendation for the management to optimalize the museum as the suitable place for conservation and source of information needed by young generation who never see those collection in their life. For that reason, dusting and regular maintenance is necessary as well as supporting facilities, safety, and create more promotion.